Further validation of the perceptions of empowerment in midwifery scale. Issue 10 (October 2015) - Pallant, J.F.; Dixon, L.; Sidebotham, M.; Fenwick, J.
Abstract Objective to assess the psychometric properties of the Perceptions of Empowerment in Midwifery Scale (PEMS) on a sample of New Zealand midwives. Design cross sectional study. Midwives completed an online survey containing the 22 item PEMS, and a number of demographic and work-related questions. Participants active practising members listed on the New Zealand College of Midwives database were invited to participate. A sample of midwives who were currently employed by an organisation was extracted (n=600). Findings exploratory factor analysis on the PEMS identified four subscales (Autonomy/Empowerment, Manager Support, Professional Support, Skills and Resources). This structure differed from that reported by the original scale developers. Each subscale showed adequate internal consistency reliability and was able to distinguish midwives who had considered leaving the profession in the past six months (p=.001). Key conclusions the psychometric properties of the revised 19-item four-subscale structure of PEMS were supported. Implications for practice The PEMS-Revised provides a psychometrically sound tool for further quantitative research to supplement the growing number of qualitative investigations of midwives perceptions and experiences of their workplace.